Gendered Laws - Hyland, Marie Caitriona (World Bank, Washington, DC, 2019)
This paper offers for the first time a global picture of gender discrimination by the law as it affects women's economic opportunity and charts the evolution of legal inequalities over five decades. Using the World Bank's newly extended Women, Business and the Law database, the paper documents large and persistent gender inequalities, especially with regard to equal pay and treatment of parenthood. The paper finds positive associations between improvements in the law and several labor market outcomes, and establishes a small, but over time increasing, causal impact of more equal laws on higher female labor force participation.